Effect of internal cleavage site mutations in human immunodeficiency virus type 1 capsid protein on its structure and function. Issue 8 (30th June 2016) - Tóth, Ferenc; Kádas, János; Mótyán, János András; Tőzsér, József
Abstract : The capsid protein of the human immunodeficiency virus type 1 has been found to be a substrate of the retroviral protease in vitro, and its processing was predicted to be strongly dependent on a pH‐induced conformational change. Several protease cleavage sites have been identified within the capsid protein, but the importance of its cleavage by the viral protease at the early phase of infection is controversial. To confirm the relevance of this process, we aimed to design, produce, and characterize mutant capsid proteins, in which the protein susceptibility toward HIV‐1 protease is altered without affecting other steps of the viral life cycle. Our results indicate that while the introduced mutations changed the cleavage rate at the mutated sites of the capsid protein by HIV‐1 protease, some of them caused only negligible or moderate structural changes (A78V, L189F, and L189I). However, the effects of other mutations (W23A, A77P, and L189P) were dramatic, as assessed by secondary structure determination or cyclophilin A‐binding assay. Based on our observations, the L189F mutant capsid remains structurally and functionally unchanged and may therefore be the best candidate for use in studies aimed at better understanding the role of the protease in the early postentry events of viral infection or retrovirus‐mediated gene transduction. Abstract : We have designed, produced, and characterized six HIV‐1 capsid single mutants showing altered protein susceptibility toward HIV‐1 protease. We studied whether these modifications affect the cyclophilin A‐binding ability and structure of the capsid protein. The introduced mutations changed the cleavage rate at the mutated sites of the capsid by the protease and caused either moderate or dramatic structural changes.